Exploring the intrinsic energy resolution of liquid scintillator to approximately 1 MeV electrons. (1st April 2022) - Deng, Y.; Sun, X.; Qi, B.; Li, J.; Yan, W.; Li, L.; Jiang, H.; Wang, C.; Cai, X.; Hu, T.; Fang, J.; Fan, X.; et al.
Abstract: We propose a novel method for exploring the intrinsic energy resolution of a liquid scintillator (LAB + 2.5 g/L PPO + 3 mg/L bis-MSB) to approximately 1 MeV electrons. With the help of coincidence detection technology, single-energy electrons of 207 Bi were effectively selected. With a careful measurement and analysis of the energy resolution of a small liquid scintillator detector, the intrinsic energy resolution of the liquid scintillator to 976 keV electrons was extracted to be 1.83% ± 0.06%. We used the wide-angle Compton coincidence (WACC) method to measure the luminescent nonlinearity of a liquid scintillator and found that it contributes only weakly to the intrinsic energy resolution of electrons. Such an unexpected large intrinsic energy resolution may come from fluctuations in energy transfer processes.